Culturas da infância nos espaços-tempos de brincar - Borba, Angela Meyer (2005)
The main objective of this study was to understand how the children, through their relations with each other during play time, make up their childhood cultures, conceptualized as forms of social action in the world promoting their identification as a particular peer group. From an ethnographic perspective, the research followed a group of children, between 4-6 years old, in a state-funded pre-school in the city of Niterói - Rio de Janeiro. Their play activities carried out in spaces and times organized by the school were observed and recorded on video and first hand note-taking. Conversation sessions with the children also took place. This research underlying principles were based on the new studies of the Sociology of Childhood, particularly, on the researches concerning children s culture. The sociological approach of childhood understands that childhood is a social construction and that children are social actors, participating actively in the construction of the society of which they are part. For this reason, the present study decided to incorporate their voices not just in the interactive-reflexive process of the participant observation, but also in the analytical interpretation of the observations. The data show that the observed group, through their peer social relations, creates a childhood culture based on the interrelationship between themselves and the institutional context. This culture is revealed by various forms of shared knowledge, which allows them to play and do things together, and by the joint construction of a social order which rules the peer relationships. Thus, the ways in which the groups are organized, the relationships between friends, the strategies used to participate in play activities (access and resistance), the negotiation of conflicts, the construction of coordinated joint actions and the relations with the school rules were analyzed and understood as elements of a child culture which identifies and organizes the group and their members in the ways they think, feel and act. The main findings of the research were synthesized through three topics trends which support some of the propositions of the Sociology of Childhood: (i) the children s agency in regulating their relations and their play activities; (ii) the desire to play together, the valorization of interactive space and sharing as central elements which participate of the construction of childhood culture; (iii) playing as a creative activity, through which children reinterpret the world and understand themselves as members of an age group and subjects of society. It is also pointed out that the recognition of the children as social actors involves the promotion and amplification of their social rights in participating in society and school institutions. This implies listening to their voices and including their ways of thinking and acting in the organization of spaces and times within these contexts.